Influence of the Load Distribution and Sizes on the Wheel Geometry in Passenger Cars - Jarosław Gonera; Jerzy Napiórkowski; Kamil Ciborowski (Communications - Scientific letters of the University of Zilina, 2021)
This paper discusses impact of changes in the load size and distribution in passenger cars on geometry of the suspension and steering systems. It was found to have a major impact on the road safety. The research was carried out with the four most popular suspension system designs used in modern passenger cars, i.e. multi-link suspension on both front and rear axles, only on the front axle, only on the rear axle and a simple suspension design for both front and rear axles. Eight load variants were used for the tests. Changes in the following wheel geometry parameters were identified: toe-in and camber angles of all the wheels and castors for the front wheels. The numerical relationships were determined between the load distribution and sizes and changes in suspension and steering systems in passenger cars. It was found that cars with multi-link suspension in both front and rear axles adapt best to changes in weight and load distribution.